THE EFFECT OF PICKING UNCERTAINTY WINDOW INTERVAL ON HYPOCENTER MICRO-EARTHQUAKE (MEQ) LOCATION USING GEIGER METHOD - Utama, Widya; Ardhya Garini, Sherly; Sere Lansa, Fradana (Journal of Marine-Earth Science and Technology, 2022)
Identification of the initial phase of the primary (P) waves at each seismic station is often inconsistent and implies the operator’s subjectivity, due to the high noise level. Errors in identifying the initial phase of the P waves can significantly bias the location of the hypocenter. In this study, the data used is one micro-earthquake (MEQ) event recorded by 8 seismic stations. At each seismic station, the P waves arrival time was measured repeatedly, to obtain the picking uncertainty time window interval of the P waves arrival time. The P waves arrival time data was processed using the Geiger method to obtain the MEQ hypocenter location. Based on the processing results, the determination of the arrival time of the P waves depends on the width of the time window and the amplitude scale used. The picking uncertainty time window interval will be narrower for arrival time observations with an enlarged time window and amplitude scale. Time window intervalin the range of 0,007-0,049 seconds, in this study significantly refracted the MEQ hypocenter location. The results of determining the location of the MEQ hypocenter using the Geiger method only produced two variants of the RMS error value with a difference of 0.001 seconds. However, the difference in the RMS error value is associated with a shift in the epicenter in the range of 2 – 21,1 meters and a shift in the elevation of the hypocenter in the range of 3-15 meters.